Determinants and Regression Equations for the Calculation of z Scores of Left Ventricular Tissue Doppler Longitudinal Indexes in a Healthy Italian Pediatric Population. (22nd November 2015) - Fibbi, Veronica; Ballo, Piercarlo; Favilli, Silvia; Spaziani, Gaia; Calabri, Giovanni B.; Pollini, Iva; Zuppiroli, Alfredo; Chiappa, Enrico
Abstract : Aim. We investigated the predictors of tissue Doppler left ventricular (LV) longitudinal indexes in a healthy Italian pediatric population and established normative data and regression equations for the calculation ofz scores. Methods and Results. A total of 369 healthy subjects aged 1–17 years (age of 6.4 ± 1.1 years, 49.1% female) underwent echocardiography. LV peak longitudinal velocity at systole (s ' ), early diastole (e ' ), and late diastole (a ' ) was determined by tissue Doppler. The ratio of peak early diastolic LV filling velocity toe ' was calculated. Age was the only independent determinant ofs ' (β = 0.491, p < 0.0001 ) and the strongest determinant ofe ' (β = 0.334, p < 0.0001 ) andE / e ' (β = - 0.369, p < 0.0001 ). Heart rate was the main determinant ofa ' (β = 0.265, p < 0.0001 ). Male gender showed no effects except for a weak association with laterals ', suggesting no need of gender-specific reference ranges. Age-specific reference ranges, regression equations, and scatterplots for the calculation ofz scores were determined for each index. Conclusion. In a pediatric Italian population, age was the strongest determinant of LV longitudinal dynamics. The availability of age-specific normality data for the calculation ofz scores may allow for correctly detecting LV dysfunction in pediatric pathological populations.